Tiilentekijöitä jäljittämässä Turun Kakskerran Poralan kylätontilla - Pellinen Hanna-Maria; Aalto Silja; Kinnunen Jussi; Tolvi Akseli; Immonen Visa (Suomen keskiajan arkeologian seura, 2022)
Kakskerta Porala is so far the earliest known Medieval deserted site in the Turku region that is knownfrom historical sources and still archaeologically preserved. It was probably abandoned in the late15th or early 16th century. During a survey of the site, a trial excavation was carried out on the north-ern edge of the settlement mound, where stone structures were visible. Excavations revealed thatit was covered throughout with soot soil. One dated structure is a large hearth-related stone cairn,perhaps originally rectangular in shape. The structure dates probably to the 14th century (1280–1421cal AD). The Medieval excavation units were rich in brick rubble and contained also some burnt clay,flint and unburnt and burnt animal bone. The site has been interpreted as evidence of brick makingby the inhabitants of the village.
Keywords: Midde Ages, villages, brick making